Alzheimer’s disease and cytokine IL-10 gene polymorphisms: is there an association? - Magalhães, Carolina Antunes; Carvalho, Maria das Graças; Sousa, Lirlândia Pires de; Caramelli, Paulo; Gomes, Karina Braga (Arquivos de Neuro-Psiquiatria, 2017)
Alzheimer’s disease (AD) is the most common form of dementia. In the last 15 years, a new theory has proposed the autoimmune mechanism as a trigger for AD. Studies on the association between AD and inflammatory biomarkers have yielded controversial results. Interleukin-10 (IL-10), an anti-inflammatory mediator, has been pointed out as one of the main cytokines associated with the occurrence of AD. Moreover, treatment that increases IL-10 levels could be a potential therapy for AD, since this cytokine acts on amyloid and pro-inflammatory molecule reduction. Based on the current literature, this study reviews evidence regarding the role of IL-10 polymorphisms in the context of AD, which has been shown to be of paramount importance for attenuating neuroinflammation, cognitive dysfunction and neurodegeneration.
Keywords: Alzheimer’s disease; inflammation; Interleukin-10